If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-3) + 2x = (-1x) + 6 -3 + 2x = (-1x) + 6 Reorder the terms: -3 + 2x = 6 + (-1x) Solving -3 + 2x = 6 + (-1x) Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '(x)' to each side of the equation. -3 + 2x + (x) = 6 + (-1x) + (x) -3 + 2x + x = 6 + (-1x) + (x) Combine like terms: 2x + x = 3x -3 + 3x = 6 + (-1x) + (x) -3 + 3x = 6 + (-1x) + x Combine like terms: (-1x) + x = 0 -3 + 3x = 6 + 0 -3 + 3x = 6 Add '3' to each side of the equation. -3 + 3 + 3x = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = 6 + 3 3x = 6 + 3 Combine like terms: 6 + 3 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| 3x-11-2x=-3 | | X+6=3x-2(x-3) | | 4x-6=-x+54 | | y=2lx-2l+7 | | f-27=4f | | -3x=19-4 | | .10(x-4)+.02x=.06x-.7 | | -12=3x-5x | | 8t^2-19t+11=0 | | -6x-6=3x-15 | | y=sqrt-9-2 | | 209=19*11+13n | | 3y^3-193=0 | | 6-8n=0 | | (X-3)(x+4)-30=0 | | 8x-5-2x+5=18+8x | | -6x+3=-45+2x | | 5+24=x+8 | | 3(y-10)+1=6(y-8) | | -4x+8=-2+x | | 5-5z=-3z | | x+3=-26+15 | | -8.2-1.7= | | 4x+2(14-x)=40 | | X=-0.142+-0.285(10.90) | | -10+x=-x+12 | | 23=b+s | | 5x(10)=81 | | N(10)+N(5)+N(0)+N(23)+N(10)= | | 15=51c-13 | | 35=-6t-7 | | -4x+5=5+7x |